Activity of an oleanane-type tritrepenoid saponin from A. glycyphyllos on human recombinant MAO enzymes - Aleksandar Shkondrov; Magdalena Kondeva-Burdina; Ivan Stambolov; Ilina Krasteva (Pharmacia, 2024)
For centuries, plants have been a leading point in the identification of potential therapeutic agents. Monoamine oxidase inhibition is a key mechanism in the treatment of various neurological and psychiatric diseases. Some triterpenoid saponins are reported to inhibit this enzyme. An extract from the aerial parts of Astragalus glycyphyllos was purified and separated by chromatographic techniques, which led to the isolation of one triterpene saponin. Its structure was analysed by ultra-high-performance liquid chromatography coupled with high-resolution electrospray ionisation mass spectrometry. The compound was subjected to a pharmacological study where human recombinant monoamine oxidase enzymes type A and B (hMAOA and hMAOB) were used. On the activity of hMAOA, the saponin had no effect, but on hMAOB, it exhibited statistically significant inhibition in comparison to the control, Selegiline. The compound could have potential in other models, so further investigations are required.